HUBUNGAN KEKUATAN OTOT TUNGKAI DAN KOORDINASI MATA DAN KAKI DENGAN AKURASI TENDANGAN KE GAWANG PADA TIM SEPAKBOLA RAJAWALI - Irwandi Ilham; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on an observation on Rajawali Football Team, the problem often being issued during a training or a game is the inimitability to score a goal. It happens because the leg muscle strength is not good enough and also the coordination between eyes and legs are not well. The purpose of this research was to find out if leg muscle strength and coordination between the eyes and legs have a correlation to the kick accuracy in the Rajawali football team. The population in this research is the entire object of research who are all football players in Rajawali football team, which consists of 18 people. Instruments in this research is leg dynamometer, eye and leg coordination and shooting test. Based on a result of a research which described in the introduction, it is concluded leg muscle has a correlation to the kick accuracy in Rajawali football team which is rhitung (0,557) > rtabel (0,468). Then from the result of the coordination of eyes and legs have a significant correlation with the accuracy of a kick in Rajawali Football Team, which result is > rtabel (0,468). The result also shows that leg muscle strength and coordination between eyes and legs have correlation on the kick accuracy in Rajawali football team, which is (0.794)> (0.468).Keywords: Leg muscle strength, leg and eye coordination, kick accuracy